CPW-fed hexagonal Sierpinski super wideband fractal antenna - Singhal S.; Singh A.K. (My University, 2025)
A compact hexagonal Sierpinski fractal antenna for super wideband applications is presented. It consists of hexagonal radiation patch with two iterations of Sierpinski square slots and coplanar waveguide feeding. An impedance bandwidth of 3.4-37.4 GHz is achieved. The achieved bandwidth ratio is 11:1. Desirable radiation performance characteristics including relatively stable and omni-directional radiation patterns are obtained over this range. A good agreement is achieved between the simulated and experimental results. The designed antenna has advantages of wider bandwidth and miniaturised size over the previously reported structures. © The Institution of Engineering and Technology 2016.